Cancer Immunoinformatics: A Promising Era in the Development of Peptide Vaccines for Human Papillomavirus-induced Cervical Cancer - Kaliamurthi, Satyavani; Selvaraj, Gurudeeban; Junaid, Muhammad; Khan, Abbas; Gu, Keren; Wei, Dong-Qing (Current Pharmaceutical Design, 2018)
Cancer immunoinformatics have led to new directions towards vaccine design from predicted potential epitope candidates, which are able to stimulate the correct cellular or humoral immune responses. They were employed to accomplish an advanced vaccine design through reverse vaccinology by replacing the whole organisms. In this review, computational tools play an essential role in evaluating multiple proteomes to identify and select the potential targeted epitopes or combinations of distinct epitopes, so that candidates may afford a rationale design competent for obtaining suitable cytotoxic T lymphocytes (CTL) or B cell-mediated immune responses. This review is a complete collection of the most beneficial online and user-friendly immunological tools, servers, and databases for the design and development of the peptide vaccine. The mechanism of major histocompatability (MHC)-restricted peptide presentation and how these tools support the vaccine development are also presented. The human papillomavirus (HPV) is taken as a model microbial strain for peptide vaccine design and its sensitization against HPV-induced cervical cancer is discussed.
Keywords: epitopes